Structural Development of Khalakan Anticline and Deposition of Dokan Conglomerate, Northeastern Iraq - Manal Shakir Al-Kubaisi; Ayyed Hussein Ward (Tikrit Journal of Pure Science)
The research shows the relation between the structural development of Khalakan Anticline and the deposition of Dokan Conglomerate. Khalakan anticline is located in NE Iraq, within the High Folded Zone of the Iraqi Western Zagros Fold – Thrust Belt, where the southwestern limb of it represents the boundary between the High Folded and Low Folded zones. The old exposed rocks in the study area ranges from the Cretaceous Qamchuqa Formation to Late Miocene Injana Formation, where these rocks form the limbs of the anticline. The young exposed rocks represented by Dokan Conglomerate, where these rocks form erosional angular unconformity with the old formations. The study shows that the growth of Khalakan Anticline occurred in Late Miocene and developed in Late Pliocene as fold related to the back-thrust fault. The study concluded that the deposition of Dokan Conglomerate in the study area is controlled by the back-thrusting through the structural development of the anticline, consequently the pliocene rivers deposited boulders size from Pila Spi Formation on the southwestern back-limb and deposited the clay size on the norteastern limb of the anticline.